Profile of defaulters and pattern of treatment default among leprosy patients at a tertiary care hospital: A 10-year analysis - Sabha Mushtaq; Devraj Dogra; Nafis Faizi; Naina Dogra (Wolters Kluwer Medknow Publications, 2020)
Background: The focus of leprosy control programs worldwide today is the WHO multidrug therapy which adequately cures the disease. Incomplete treatment puts not only the patient but the entire community at risk which may further jeopardize the leprosy control program. Objective: To study the magnitude of treatment default among leprosy patients, its trend in the last 10 years, and association with clinicodemographic variables. Materials and Methods: This was a retrospective study conducted at the urban leprosy center (ULC) attached to the dermatology department of a tertiary care centre. Data were obtained from the standard leprosy cards maintained at ULC from 2005-14. The following data were collected from the preformatted cards: age, gender, residence, occupation, type of leprosy, treatment, time of default, and so on and analyzed to see the association of defaulter status with sociodemographic and disease-related variables. Results: In a total of 743 cases, the rate of treatment default was 39.3%. The default status was found to have decreased significantly over the years from 2005-14 (P = 0.03). Majority of the treatment defaulters were migrants (47.9%) as compared with natives (29.7%) (P < 0.001). Regardless of the residential status, treatment default was more in pure neuritic (58.5%) and tuberculoid type (40.7%) as compared with others (P < 0.001). Smear negative cases (40.0%) were more likely to default than smear-positive cases (31.4%) (P < 0.001). Rate of defaulting was more among patients in the district where ULC was located than in the districts away from ULC (P = 0.017). Conclusion: Though the study period witnessed an overall decreasing trend over the 10-year period, treatment default remains a major concern in leprosy. Adherence to treatment is central to the success of leprosy control programs and therefore the factors associated with defaulting from treatment need to be addressed.